New Paradigm of Rajabhat University for Local Development - ทวีกุล, วัชราภรณ์ (Journal for Developing the Social and Community, 2016)
Rajabhat University will be able to develop as the University for developing locality according to principle of Rajabhat University Act 2004 positively, it needs to adapt in several dimensions; (1) Policy and Management ; The university policy should be strengthened to meet the University's mission for local development, (2) Graduates Production ; the curriculum should be tailored to meet the needs and needs of the locality, (3) Research ; prepare guidelines for promoting research are set up by setting up research frameworks related to research for local development, (4) Academic Services : Strategic plans for academic services should be defined by determining the specific agency to service, (5) Local Arts and Culture Reservation and Maintain